Pengaruh Efisiensi Energi Listrik pada Sektor Industri dan Komersial terhadap Permintaan Listrik di Indonesia - Mulyani, Dini; Hartono, Djoni (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No.1, Februari 2018 (pp. 1-144)DO - 10.24843/JEKT.2018.v11.i01.p01, 2018)
Effective and efficient electricity consumption is one of the main concerns of Indonesian government. Indonesian electricity consumption has been growing rapidly in the last decade. It is predicted that total electricity consumption will continue grow with faster growth rate. Therefore, immediate actions on the demand side arenecessary through electricity consumption efficiency. The study employs a dynamic panel approach on the panel data of 31 provinces in Indonesia during the period 20014-2013. The results suggest that aggregate electricity demand can be reduced through efficiency on electricity consumption in industrial and commercial sector. The study also reveals that real GRDP, population, and changes in the economic structure have a positive and significant impact on the electricity demand. On the other hand, the effect of real electricity price on electricity demand is not statistically significant.